THE EFFECT OF SELF-REGULATED LEARNING ON STUDENTS’ PROBLEM-SOLVING ABILITIES - Sri Rahayuningsih; Muhammad Hasbi; Mulyati Mulyati; Muhammad Nurhusain (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
Abstract The present study aimed to 1) investigate the effect of self-regulated learning on students’ mathematical problem-solving ability; 2) describe the cognitive processes carried out by students with low and high self-regulation and high problem-solving ability. This study employed an explanatory mixed-method design. Nineteen students at a private high school, in Makassar, Indonesia, were selected, in order to complete the questionnaire, mathematical problem-solving ability test. Of the 19 students, two were selected as research subjects representing problem-solving ability. The quantitative data were analyzed using descriptive statistics and inferential statistics, while the qualitative data analysis had to go through the following stages including, reduction, data display, and conclusion drawing. The results showed that 1) self-regulated learning had no effect on students’ mathematical ability; 2) the cognitive processes carried out by students with high self-regulation and high problem-solving ability included high literacy ability, high metacognitive awareness, being proactive yet inflexible; 3) the cognitive processes carried out by students with low self-regulation and high problem-solving ability included low literacy ability but showing more flexible attitudes. From this study, it can be concluded that problem-solving ability is not influenced by self-regulated learning, but by other factors such as the environment, cognitive ability and cognitive preparedness. Keywords: Problem-solving ability; self-regulated learning. Abstract Penelitian ini bertujuan untuk 1) menginvestigasi pengaruh self-regulated learning terhadap kemampuan pemecahan masalah matematis siswa; 2) mendeskripsikan proses kognitif yang dilakukan siswa dengan self-regulation rendah dan tinggi dan kemampuan pemecahan masalah tinggi. Penelitian ini menggunakan explanatory mixed-method design. Sembilan belas siswa sekolah menengah swasta, di Makassar, Indonesia, dipilih untuk mengisi angket tes kemampuan pemecahan masalah matematika. Dari 19 siswa tersebut, dipilih dua orang sebagai subjek penelitian yang mewakili kemampuan pemecahan masalah. Data kuantitatif dianalisis menggunakan statistik deskriptif dan statistik inferensial, sedangkan analisis data kualitatif melalui tahapan yaitu, reduksi data, menampilkan data, penarikan Kesimpulan. Hasil penelitian menunjukkan bahwa 1) self-regulated learning tidak berpengaruh terhadap kemampuan matematika siswa; 2) proses kognitif yang dilakukan siswa dengan self-regulated learning tinggi dan kemampuan pemecahan masalah tinggi meliputi kemampuan literasi tinggi, kesadaran metakognitif tinggi, proaktif namun tidak fleksibel; 3) Proses kognitif yang dilakukan siswa dengan self-regulated learning rendah dan kemampuan pemecahan masalah tinggi meliputi kemampuan literasi rendah tetapi menunjukkan sikap lebih fleksibel. Dari penelitian ini dapat disimpulkan bahwa kemampuan pemecahan masalah tidak dipengaruhi oleh self-regulated learning, melainkan oleh faktor lain seperti lingkungan, kemampuan kognitif, dan kesiapan kognitif. Keywords: Kemampuan pemecahan masalah, self-regulated learning.